Acute Complicated Brucellosis Mimicking Crimean-Congo Hemorrhagic Fever (CCHF) and Vice Versa - Ali akbar Heydari (Pasteur Institute of Iran, 2019)
Brucellosis and Crimean Congo Hemorrhagic Fever (CCHF) are both common zoonoses that may co-occur in similar epidemiological conditions, e.g., among young livestock breeders, veterinarians, and farmers in rural areas. Transmission of Brucella bacteria is through ingestion of contaminated dairy products, while CCHF virus infection occurs via infective tick bite or exposure of damaged skin and mucosa to the tissues and blood of viremic animals. Brucellosis occurs almost in all seasons, while CCHF is of lower incidence in the cold seasons due to decreased activity of tick vectors. CCHF mimics brucellosis and vice versa, mainly when the latter manifests severe thrombocytopenia and hemorrhage. Occasionally, the two illnesses present similar clinical features and laboratory results, e.g., fever, muscle aches, increased liver enzymes, and thrombocytopenia. This article discusses the similar clinical, epidemiological and laboratory aspects of the two diseases and warns physicians to avoid the inappropriate use of drugs such as ribavirin, which is dangerous in patients with kidney failure and pregnancy.